Philosophical Overview of Freedom of Expression in The Implementation of Islamic Education Management - Andriani, Rina; Wardhana, Kautsar Eka (Poltanesa, 2023)
This research discusses a philosophical examination of freedom of expression in the context of the implementation of Islamic education management. Freedom of expression becomes a crucial aspect in the development of a dynamic and innovative work environment. Through a philosophical approach, this research analyzes the concept of freedom of expression in the context of management, identifies its impact on decision making, and evaluates the role of management in supporting freedom of expression. This article aims to conduct a philosophical review of freedom of expression in the context of the implementation of Islamic education management. The main focus of this research is to delve into the concept of freedom of expression within the framework of Islamic values and how this concept can be integrated into educational management. The research uses philosophical analysis and literature methods to explore the views of Islamic philosophers regarding freedom of expression and identify the relevance of this concept in the administration of Islamic educational institutions. However, this freedom is not absolute but is limited by Islamic moral and ethical values. The concept of freedom of expression in Islamic education management requires a profound understanding of Islamic values, in line with the educational objectives desired in the context of religious teachings.